INSTITUTIONAL ROLE OF PUBLIC ASSOCIATIONS IN THE FORMATION AND IMPLEMENTATION OF STATE POLICY ON PHYSICAL EDUCATION IN UKRAINE - STEPYUK, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive study of the institutional role of public associations in the formation and implementation of state physical education policy in Ukraine in the context of socio-political transformations and European integration processes. The relevance of the topic is due to the strengthening of the role of civil society institutions in the implementation of policies aimed at the development of physical culture and a healthy lifestyle, as well as the need to increase the efficiency of the implementation of state programs in the field of physical education, especially in the context of limited budget resources and the growing demand of the population for access to quality sports and health services. The theoretical basis of the study is based on the concepts of partnership between the state and civil society, decentralization of management and institutional interaction. The purpose of the study is to determine the place and functional significance of public associations in the system of public management of physical education, identify barriers to the effective implementation of their powers, and substantiate the directions of strengthening their influence on the formation of policy in this area. The paper analyzes the regulatory framework that determines the legal status and opportunities for public associations to participate in state management of physical culture, in particular the Law of Ukraine “On Physical Culture and Sports”, the Decree of the President of Ukraine “On the National Doctrine for the Development of Physical Culture and Sports” and other acts. Particular attention is paid to the practical aspects of implementing state programs with the participation of public organizations, in particular the analysis of project activities, the organization of mass events, increasing the level of physical activity of various social groups, as well as working with youth, people with disabilities and other vulnerable categories of the population. The study is based on empirical data, in particular statistics on the participation of the population in sports events, data on the number of active public organizations in the field of physical culture, the amount of state support, as well as on the analysis of cases of successful cooperation between authorities and the public sector in the regions of Ukraine. The article identifies the main problems that hinder the effective participation of public associations in the implementation of state policy: imperfect regulatory regulation, lack of stable funding, low level of staffing, weak institutional capacity, as well as insufficiently formed feedback mechanisms between the authorities and civil society. A number of practical recommendations are proposed to strengthen the institutional capacity of public organizations: improving the legislative framework, introducing targeted funding mechanisms, developing human capital development programs in the public sector, creating platforms for sustainable partnerships between authorities, educational institutions and public associations.
Keywords: public associations; physical education; state policy; public administration; institutional capacity; sports activity; social partnership; physical culture; decentralization; public participation; sport for all; civil society